Knowledge on acute respiratory infection alarm signs of mothers of children under five years old. Servicio Desconcentrado Hospital Universitario Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2020)
With the objective of determining the level of knowledge that mothers have about warning signs of acute respiratory infections (ARI) in children under 5 years of age who attended the Servicio Desconcentrado Hospital Universitario Pediátrico Dr. Agustín Zubillaga (November, 2019), a cross-sectional descriptive study was carried out with 37 mothers with an average age of 29.2 ± 7.3 years, 43.2% were single, with completed secondary school (27%) and employed (40.5%). Average age of patients was 15.3 ± 6.2 months with male predominance (54%); during the previous year, 45.9% had between 2-3 episodes of ARI. Level of knowledge of mothers about global warning signs of ARI was regular in 56.76% of cases. Regarding causes of ARI, level of knowledge was insufficient in 48.6% of mothers. Warning signs of ARI identified by the mothers were, in order of frequency, difficulty in breathing (91.8%), fever (81%), food rejection (78.3%) and loud breathing loud (75.6%). In conclusion, it is clear that most mothers know the main warning signs of ARI however intervention strategies should be established to improve knowledge in order for mothers to recognize early warning signs and therefore seek attention in a timely manner.
Keywords: acute respiratory infections; fever; dyspnea; pneumonia; warning signs